A Case Study to Evaluate the Role of Trayaushnadi Vati in the Management of Madhumeha (Type 2 Diabetes Mellitus) - Manhas Ekta; Kumar Sanjeev; Singh Kumar Anil (AYUSHDHARA, 2023)
India is known as the diabetes capital of the world. By 2025, the country's diabetes population will have risen to 69.9 million, and by 2030, it will have risen to 80 million. This means that the developing country is anticipated to have a 266% gain. In the present study, a 35-years-old obese male patient came to the OPD with complaints of Daurbalyata (weakness), Atimutrata (increased frequency of micturition) and Atitrishna (excessive thirst) since seven days. The diagnosis leads to Madhumeha (Type 2 Diabetes mellitus) through physical findings and biochemical investigations. The treatment plan opted for was Trayaushnadi Vati with a change in diet and lifestyle. This case study emphasizes the usefulness of Ayurveda and it aims to detoxify, purify, strengthen and balance the body Dosha (regulatory functional factors of the body) of the body Dhatus (major structural components of the body) to attack the root cause and ensure complete healing. Several medicinal herbs appear to be as beneficial as traditional anti-diabetic medications in lowering HbA1c levels. To determine the benefits of prospective plant-based medicines on diabetes, rigorous trials with at least 3 months of follow-up are required.